Straw dogs [videorecording (DVD)] - Lurie, Rod, 1962-; Skarsgård, Alexander; Purcell, Dominic, 1970-; Marsden, James, 1973-; Woods, James, 1947-; Bosworth, Kate, 1983- (Columbia TriStar Home Entertainment, 2011)
David and Amy Sumner, a Hollywood screenwriter and his actress wife, return to her small hometown in the deep South to prepare the family home for sale after her father's death. Once there, tensions build in their marriage and old conflicts re-emerge with the locals, including Amy's ex-boyfriend Charlie, which leads to a violent confrontation.